Remnant kelp bed refugia and future phase-shifts under ocean acidification. - Scott D Ling; Christopher E Cornwall; Bronte Tilbrook; Catriona L Hurd (PLoS ONE, 2020)
Ocean warming, ocean acidification and overfishing are major threats to the structure and function of marine ecosystems. Driven by increasing anthropogenic emissions of CO2, ocean warming is leading to global redistribution of marine biota and altered ecosystem dynamics, while ocean acidification threatens the ability of calcifying marine organisms to form skeletons due to decline in saturation state of carbonate Ω and pH. In Tasmania, the interaction between overfishing of sea urchin predators and rapid ocean warming has caused a phase-shift from productive kelp beds to overgrazed sea urchin barren grounds, however potential impacts of ocean acidification on this system have not been considered despite this threat for marine ecosystems globally. Here we use automated loggers and point measures of pH, spanning kelp beds and barren grounds, to reveal that kelp beds have the capacity to locally ameliorate effects of ocean acidification, via photosynthetic drawdown of CO2, compared to unvegetated barren grounds. Based on meta-analysis of anticipated declines in physiological performance of grazing urchins to decreasing pH and assumptions of nil adaptation, future projection of OA across kelp-barrens transition zones reveals that kelp beds could act as important pH refugia, with urchins potentially becoming increasingly challenged at distances >40 m from kelp beds. Using spatially explicit simulation of physicochemical feedbacks between grazing urchins and their kelp prey, we show a stable mosaicked expression of kelp patches to emerge on barren grounds. Depending on the adaptative capacity of sea urchins, future declines in pH appear poised to further alter phase-shift dynamics for reef communities; thus, assessing change in spatial-patterning of reef-scapes may indicate cascading ecological impacts of ocean acidification.